FEATURES OF REGIONAL PRODUCTION OF SUNFLOWER SEEDS IN THE PERIOD 1990-2021 IN UKRAINE - Oksana MAKARCHUK; Tetyana KUTS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper aims to provide analysis of the main features of regional production of sunflower seeds in Ukraine. To realize aims in the article, the importance of agriculture was pointed and evaluation of sunflower seeds productions in accordance with natural and climatic zones were done. Results showed that areas under sunflower have increased significant and in 2021 there was observed the share of 52% of the harvest collected by agricultural enterprises in the Steppe zone, 39% in the Forest-steppe zone, and 9% in the Polissya zone. Grouping enterprises under the area size of sunflower growing confirmed the fact that the bigger arable land of sunflower has the enterprise, the more productive will be sunflower production, in particular, enterprises that have arable land under sunflower more than 2000 ha get yield more than 24 centners per hectare. These enterprises have possibilities to use new technologies to achieve the desired effect during production. The area and introduced pesticides factors was taken into account in regression analysis due to the importance of both them in increasing sunflower seeds production. Results showed close dependence between mentioned factors. In the article discussed a few aspects regarding the sunflower seeds market in Ukraine under the condition of the hostilities in the region. There are evaluated experts opinions regarding production capacities, processing, export and prices on the domestic and world market.